His Excellency The Governor's Residence, St. Ann's, Trinidad, B.W.I. - Dalla Costa, H. (Y. De Lima and Co. Ltd., Trinidad, 2009)
A painting of the Governor's Residence surrounded by the tropical flora of the Botanical Gardens with the flag of the United Kingdom flying at full mast and the green St. Ann's hills filling the background. The postcard is addressed to A. Merino, Sacramento, California, U.S.A. Affixed to the postcard is a Suriname 10C stamp, postmarked 1955. Postcard number 88369.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Flags--Great Britain; 1955; Architecture--Trinidad and Tobago; Gardens--Trinidad and Tobago; President's House, The